A pilot investigation of the efficacy and safety of magnesium chloride and ethanol as anesthetics in Loligo vulgaris embryos - Sprecher, Marta; Sprecher, Simon G.; Spadavecchia, Claudia (Frontiers in Physiology, 2022)
The inclusion of cephalopods in the legislation related to the use of animals for experimental purposes has been based on the precautionary principle that these animals have the capacity to experience pain, suffering, distress, and lasting harm. Recent studies have expanded this view and supported it. Handling cephalopod mollusks in research is challenging and whenever more invasive procedures are required, sedation and/or anesthesia becomes necessary. Therefore, finding adequate, safe, and effective anesthetics appears mandatory. Several substances have been considered in sedating cephalopods, in some instances applying those utilized for fish. However, species-specific variability requires more detailed studies. Despite long-lasting experience being linked to classic studies on squid giant axons, evidence of action on putative anesthetic substances is scarce for Loligo vulgaris and particularly for their embryos. The aim of the current study was to evaluate effects elicited by immersion of squid embryos in anesthetic solutions and examine whether these forms display a similar reaction to anesthetics as adults do. Different concentrations of ethanol (EtOH; 2, 2.5, and 3%) and magnesium chloride (MgCl2; 1, 1.5, and 1.8%) were tested by adopting a set of indicators aimed at exploring the physiological responses of squid embryos. Forty-two embryos of the common squid Loligo vulgaris (stages 27–28) were assigned to three conditions (EtOH, MgCl2, and controls) and video recorded for 15 min (5 min before, 5 min during, and 5 min after immersion in the anesthetic solutions). In each group, the heart rate, respiratory rate, buoyancy, chromatophore activity, and tentacles/arms responses were assessed to evaluate the embryos' vitality and responsiveness to stimulation. Both substances provoked a decrease in heart and respiratory rates and inhibited buoyancy, chromatophores, and tentacles/arms responses; no adverse effects were observed. EtOH had a faster onset of action and faster recovery than MgCl2, being potentially more adequate as an anesthetic for shorter procedures. Even though MgCl2 caused a longer muscle relaxation, the reversibility was not confirmed for the 1.8% concentration; however, lower concentrations triggered similar results as the ones obtained with the highest EtOH concentrations. We have shown that the late developmental stages of Loligo vulgaris embryos could represent a good model to evaluate anesthetics for cephalopods since they can display similar reactions to anesthetics as adults animals do.